Impact of COVID-19 on migrants' access to primary care and implications for vaccine roll-out: a national qualitative study - Knights, Felicity; Carter, Jessica; Deal, Anna; Crawshaw, Alison F; Hayward, Sally E; Jones, Lucinda; Hargreaves, Sally (British journal of general practice, 2021)
COVID-19 has led to big changes in UK primary care, including rapid digitalisation, with unknown impact on migrant groups. To understand the pandemic's impact on recently-arrived migrants and their access to primary health care, and implications for vaccine roll-out. Qualitative study involving semi-structured interviews with primary care professionals (PCPs) and migrants in urban, suburban, and rural settings across England. Sixty-four PCPs and administrative staff, and 17 recently-arrived migrants were recruited using purposive, convenience, and snowball sampling. In-depth, semi-structured interviews were conducted by telephone. Data were analysed iteratively, informed by thematic analysis. PCPs and migrants concurred that digitalisation and virtual consultations have amplified existing inequalities in access to health care for many migrants, due to a lack of digital literacy and access to technology, compounded by language barriers. PCPs were concerned that virtual consultations resulted in difficulties building trust and risked missing safeguarding cues. Both PCPs and migrants highlighted challenges around registering and accessing health care due to physical closure of surgeries, as well as indirect discrimination, language and communication barriers, and a lack of access to targeted and tailored COVID-19 information or interventions. Migrants reported a range of specific beliefs, from acceptance to mistrust, around COVID-19 and potential COVID-19 vaccines, often influenced by misinformation. Innovative opportunities were suggested, including translated digital health advice using text templates and YouTube; these merit further exploration. Pandemic-related changes to primary care delivery may become permanent; some migrant groups are at risk of digital exclusion and may need targeted additional support to access services. Solutions are needed to address vaccine hesitancy in marginalised groups to ensure equitable COVID-19 vaccine uptake.